Dampak Banjir Terhadap Kondisi Ekonomi Dan Kesehatan Keluarga: Study Kasus di Kelurahan Sri Meranti dan Meranti Pandak Pekanbaru - Zakya HS , Ismon; Harahap, Heryudarini (IPTEKIN Jurnal Kebijakan Pembangunan dan Inovasi, 2015)
Flood disasters is almost inevitable in every rainy season. In Pekanbaru city, the area that became flooding ‘subscription’ is generally located on the edge of the river Siak. The aim of the analysis was to determine the impact of flooding on the economic and health of household at Sri Meranti and Meranti Pandak Pekanbaru City in 2014. Respondents were household in both the village and always flooded during the rainy season. The number of household that were analyzed were 416 people. The study design was cross-sectional. The data were analyzed descriptively. The analysis showed that the proportion of household that experienced decline in income was 48.8%, and expenditure was increased 69.0% when flooding occurs. The combination of income and expenditure showed 78.1% of household experiencing changes in economic conditions which consist of 1) regularly income – increase expenditure was 29.3%, 2) decrease income – regularly expenditure was 9.1% and 3) decrease income – increase expenditure at 39, 7%. When flooding, 89.7% of household had health problem. The illness was itchy 93.6%, fever 80.7%, malaria 24.1%, and other diseases 12.9%. Fever was significantly (p